MEANS OF PROTECTING VICTIMS OF CRIME AT EUROPEAN LEVEL - Palade-Ropotan , Mihaela (International Journal of Legal and Social Order, 2025)
In the last half-century, the crystallization of the European Union has also led to the gradual easing of border crossing conditions, so that, along with the possibility of more frequent travel for a large number of people, the phenomenon of crime has also increased, with extensions across the territory of two or even more states. Proportionally, the number of victims of these categories of crime has also increased, victims for whom it is still difficult to gain access to justice or obtain any other type of compensation as a result of the negative events they have experienced. Although considerable efforts are being made at legislative level to cover the rights that a victim should have and avail of, at operational level there are still shortcomings which reduce the chances that victims, especially vulnerable victims, will be able to benefit from specialized legal assistance, compensation for damages or a minimum level of protection.